2020
DOI: 10.3390/en13215853
|View full text |Cite
|
Sign up to set email alerts
|

Approximation Algorithm-Based Prosumer Scheduling for Microgrids

Abstract: Since the inherent intermittency and uncertainty of renewable energy resources complicates efficient Microgrid operations, a Demand Response (DR) scheme is implemented for customers in the grid to alter their power-usage patterns. However, for a real-time pricing model at the current DR, the automated decision on the energy price is not trustworthy because of artificial interferences to the power generation. As opposed to energy price, an operational cost-based prosumer scheduling approach would be able to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Regarding the computational effort, the study carried out in [32] concluded that prosumer scheduling in microgrids is a NP-hard problem, for which optimization algorithms will find approximate solutions. It follows that, if the prosumer management is formulated as an optimization problem, the computational-intensive classical algorithms could be successfully replaced with other methods with marginal performance decrease.…”
Section: Related Literaturementioning
confidence: 99%
“…Regarding the computational effort, the study carried out in [32] concluded that prosumer scheduling in microgrids is a NP-hard problem, for which optimization algorithms will find approximate solutions. It follows that, if the prosumer management is formulated as an optimization problem, the computational-intensive classical algorithms could be successfully replaced with other methods with marginal performance decrease.…”
Section: Related Literaturementioning
confidence: 99%
“…Both approaches were carried out in a regulatory context in Spain and contributed to the efficient performance of the electricity grid. To minimize the total operational costs of a set of prosumers in the EDN, the authors in [34] developed strategies based on the Directed Steiner Tree (DST) and Weighted Dominating Set (WDS) algorithms. In this work, the economic and operational constraints of each microgrid belonging to a given prosumer were considered in formulating the problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the computational standpoint, the current research shows that prosumer management is difficult to solve accurately. A study [31] concluded that prosumer scheduling in microgrids is an NP-hard problem, to which approximate solutions can be found. Thus, if the prosumer management problem (PSM) can be formulated as an optimization problem, the computation-intensive classical optimization algorithms can be replaced with other methods with a minimal tradeoff in accuracy.…”
Section: Introductionmentioning
confidence: 99%